The Impact of COVID-19 on Self-Reported Substance Use, Well-Being, and Functioning Among United States Veterans: A Cross-Sectional Study - Reilly, Erin D.; Chamberlin, Elizabeth S.; Duarte, Brooke A.; Harris, J. Irene; Shirk, Steven D.; Kelly, Megan M. (Frontiers in Psychology, 2022)
As the COVID-19 pandemic sweeps the globe, many veterans with substance use issues have faced the closure of treatment facilities, mandates to shelter in place, and social distancing measures. To better understand their pandemic experiences, substance use changes, and functioning, a survey was nationally administered to a sample of U.S. veterans reporting substance use issues during the pandemic. The purpose of this cross-sectional online survey for veterans (N = 409) was to report on COVID-19 experiences, safety behaviors, and infection experiences while also investigating the relationship among addictive behaviors, mental and physical health, and COVID-19 impact. Measures also assessed specific substance use concerns, pandemic-related loneliness, and functioning. Though few veterans reported personally receiving a confirmed COVID-19 medical diagnosis (10.5%), the impact of pandemic stressors was evident, with a majority reporting anxiety related to contracting COVID-19 (61.4%) or fear of a family member or close friend contracting COVID-19 (58.7%). Participants reported increased use of alcohol (45.3%), sedatives (36.6%), inhalants (35.7%), tobacco (35.0%), and cannabis (34.9%), attributed specifically to the pandemic. Regression analyses revealed that even when controlling for the contribution of problematic substance use issues, negative pandemic impacts and self-reported COVID-19 related loneliness were related to more impaired physical and mental health functioning during the pandemic. Findings from this sample of veterans with addiction issues add to the growing literature suggesting unique and adverse effects of COVID-19 stressors on functioning while also revealing specific pandemic impacts for this group.